Quir : il bimestrale fiorentino di cultura e vita lesbica e gay. (Firenze : Arcigay Arcilesbica, 1996)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks?Redactie : Via del Leone 5/11r, 50124 Firenze
Italiaans
Periodiek